Preserving Romantic Relationship in the Age of Social Media - Leandro C. Torreon (Current Progress in Arts and Social Studies Research Vol. 5, 2024)
The use of telephones and computers has paved the way for the recent addition to communication, the social networking platform (SNS). Facebook is one of the most popular social networking sites (SNS) that recreates face-to-face interactions on the web by allowing people to interact publicly or privately. This research explored the role of social media in preserving romantic relationships among university faculty, staff, and students. The study, employing a descriptive survey and correlational design, investigated the relationship between social media use and romantic relationship outcomes. The study was conducted at the Bohol Island State University (BISU) Candijay Campus, Cogtong, Candijay, Bohol, Philippines. A questionnaire assessed participants’ Facebook usage patterns and their romantic relationships, focusing on aspects like partner surveillance, relationship satisfaction, self-disclosure, and social intimacy. Most of the respondents were female who covered the major populace in the university and dominated the number of populations in school with fifty-seven (57) or 76%. The result indicated that respondents value the importance of understanding in maintaining relationships. The findings indicated a slight positive correlation between partner surveillance on Facebook and relationship satisfaction. This suggests that increased partner surveillance on the platform might lead to greater relationship satisfaction, while a lack of it could potentially contribute to relationship strain. However, the study also acknowledged that other factors, such as affectionate communication, play a significant role in relationship satisfaction. Based on these results, the research recommends that strong communication and interaction between partners are crucial for maintaining healthy romantic relationships, even in the context of social media platforms like Facebook; there is a need for a school program to guide the students, faculty, and staff in handling healthy relationship and affectionate communication shall be given value in maintaining a romantic relationship.